Penggunaan Slack Dalam Kolaborasi Dan Komunikasi Organisasi Siswa Intra Sekolah (OSIS) di SMK PGRI Sukodadi Lamongan [The Use of Slack in Collaboration and Communication of the Student Organization (OSIS) at SMK PGRI Sukodadi Lamongan] - Fajar Annas Susanto; Nilam Cahya; M. Ramadhani Tejakumara; Reyhan Dicko Putra E; Anugrah Ushofiyah B (Indonesia Berdaya, 2026)
The digital era demands the optimization of technology to support the educational process, especially in communication and collaboration. This study aims to improve the effectiveness of communication and collaboration at SMK PGRI Sukodadi Lamongan through the implementation of the Slack application. The method used is community service with a model of training, mentoring, and evaluation of Slack implementation for teachers and staff. The results show significant improvements in digital literacy, communication effectiveness, and collaborative learning. Slack has proven to provide a centralized solution for information dissemination, task coordination, and academic interaction. This implementation also demonstrates an increase in employees' soft skills such as digital communication and teamwork. The study concludes that Slack can be an effective alternative in supporting digital transformation in the educational environment. Abstrak. Era digital menuntut optimalisasi teknologi dalam mendukung proses pendidikan, terutama dalam hal komunikasi dan kolaborasi. Penelitian ini bertujuan untuk meningkatkan efektivitas komunikasi dan kolaborasi di SMK PGRI Sukodadi Lamongan melalui implementasi aplikasi Slack. Metode yang digunakan adalah pengabdian masyarakat dengan model pelatihan, pendampingan, dan evaluasi penerapan Slack bagi guru pegawai. Hasil kegiatan menunjukkan peningkatan signifikan dalam literasi digital, efektivitas komunikasi, dan kolaborasi pembelajaran. Slack terbukti memberikan solusi terpusat dalam penyebaran informasi, koordinasi tugas, dan interaksi akademik. Implementasi ini juga memperlihatkan peningkatan soft skill pegawai seperti komunikasi digital dan kerja tim. Penelitian ini menyimpulkan bahwa Slack dapat menjadi alternatif efektif dalam mendukung transformasi digital di lingkungan pendidikan.